Intratracheal Keratinocyte Growth Factor Enhances Surfactant Protein B Expression in Mechanically Ventilated Preterm Pigs - Krishnan, Ramesh; Arrindell, Esmond L.; Frank, Caminita; Jie, Zhang; Buddington, Randal K. (Frontiers in Pediatrics, 2021)
Bronchopulmonary dysplasia (BPD) is a devastating disease of prematurity that is associated with mechanical ventilation and hyperoxia. We used preterm pigs delivered at gestational day 102 as a translational model for 26–28-week infants to test the hypothesis administering recombinant human keratinocyte growth factor (rhKGF) at initiation of mechanical ventilation will stimulate type II cell proliferation and surfactant production, mitigate ventilator induced lung injury, and reduce epithelial to mesenchymal transition considered as a precursor to BPD. Newborn preterm pigs were intubated and randomized to receive intratracheal rhKGF (20 µg/kg; n=6) or saline (0.5 ml 0.9% saline; control; n= 6) before initiating 24 hours of ventilation followed by extubation to nasal oxygen for 12 hours before euthanasia and collection of lungs for histopathology and immunohistochemistry to assess expression of surfactant protein B and markers of epithelial to mesenchymal transition. rhKGF pigs required less oxygen during mechanical ventilation, had higher tidal volumes at similar peak pressures indicative of improved lung compliance, and survival was higher after extubation (83% vs 16%). rhKGF increased surfactant protein B expression (p< 0.05) and reduced TGF-1β (p< 0.05), that inhibits surfactant production and is a prominent marker for epithelial to mesenchymal transition. Our findings suggest intratracheal administration of rhKGF at initiation of mechanical ventilation enhances surfactant production, reduces ventilator induced lung injury, and attenuates epithelial-mesenchymal transition while improving pulmonary functions. rhKGF is a potential therapeutic strategy to mitigate pulmonary responses of preterm infants that require mechanical ventilation and thereby reduce the incidence and severity of bronchopulmonary dysplasia.